Bioactive Polysaccharides from Hericium erinaceus: Extraction, Structure, Bioactivities, and Applications - Fangzhi Ge; Yan Chen; Binshuo Wang; Wenxin Zhou; Baoxiang Du; Lin Hou (Molecules)
Hericium erinaceus, an edible fungus belonging to the family Odontaceae, is predominantly found in Western Europe, North America, and East Asia. In China, it primarily thrives in the mountainous and forested regions in the northeast, north, and southwest. Historically, Hericium erinaceus has served as a medicinal and nutritional entity. Its mycelia and fruiting bodies are the products of its vegetative growth stage and reproductive growth stage, respectively. The principal active components are different Hericium erinaceus polysaccharides (HEPs), which are a group of polysaccharides primarily composed of galactose, glucose, and a small amount of mannose and fucose. An extremely small number of HEPs contain fructose, glucuronic acid, xylose, arabinose, and other components. The common extraction method employed is water extraction followed by alcohol precipitation. HEPs exhibit a diverse array of biological activities, including immune enhancement, anti-tumor effects, anti-inflammatory properties, antioxidant capabilities, and antiviral functions. This paper provides a comprehensive review of recent advancements in the extraction, separation, purification, structural analysis, biological activity, and toxicity assessments of HEPs. Additionally, it discusses the opportunities and challenges associated with scientific research and practical applications in this field.